Late quaternary activity characteristics of the Quzika-Jitang segment along the Lancangjiang fault zone, eastern Tibetan Plateau - Han, Mingming; Wang, Shiyuan; Li, Yanbao; Chen, Lichun; Li, Xuemei; Wang, Dongbing; Zeng, Xiaowen (Frontiers in Earth Science, 2025)
The Lancangjiang fault zone (LCJFZ) is a major crustal-scale fault system that traverses the Sichuan-Tibet traffic corridor. Determining its late Quaternary activity is thus crucial for assessing seismic hazards and guiding the planning of this critical infrastructure. However, there is no clear evidence as to whether the fault zone has been active since the late Quaternary. Although recent studies have suggested that the Lancangjiang fault (LCJF), a main branch of the LCJFZ, offsets Holocene sediments near the Jitang and Quzika sites and is therefore active, the supporting evidence remains inconclusive. In this paper, we carried out detailed field investigation along the Quzika-Jitang segment, building on previous work. Combined with radiocarbon dating, we reassessed the late Quaternary activity of the LCJF. Our new results reveal that the nearly SN-trending segment of the LCJF (F1) shows no sign of late Quaternary activity. In contrast, the NE-trending branch fault of the LCJF (F2), located near Quzika Township, has faulted the late Quaternary strata and may exhibit Holocene activity. Further analysis suggests that the LCJFZ is no longer the main structure regulating regional tectonic deformation. Instead, secondary strike-slip faults, such as fault F2 and the Yangda-Yaxu fault (YYF), cut through or intersect the LCJFZ, and exhibit obvious late Quaternary activity. Thus, we speculate that the NE-trending F2 and WNW-trending YYF are both probably the most active structures around the LCJFZ today. These observations indicate that the main structures absorbing and regulating regional strain energy have changed from nearly SN-trending LCJFZ to several secondary WNW- and NE-trending faults, which means that tectonic transformation and fault neogenesis have occurred around the LCJFZ.